UV paint coating process for aluminum template
By polishing, corrosion, photocuring and electron beam curing on the surface of the aluminum formwork, the corrosion problem of aluminum formwork in harsh environments is solved, and the adhesion and corrosion resistance of the coating are significantly improved, the service life of the aluminum formwork is extended and the surface quality of the concrete wall is improved.
Patent Information
- Application Number
- CN202510098244.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-11
AI Technical Summary
Aluminum formwork is prone to corrosion in harsh environments, causing the coating to fall off, affecting the quality of the project and the reusable service life of the formwork.
By polishing, corrosion, photocuring and electron beam curing on the surface of the aluminum template, the adhesion between the coating and the aluminum template and the strength of the coating itself are improved.
It significantly improves the adhesion and corrosion resistance of the coating, allowing the coating to protect it for a long time in harsh environments, extends the service life of aluminum formwork and improves the surface quality of concrete walls.
Smart Images

Figure BDA0005253443990000061 
Figure BDA0005253443990000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum template anti-corrosion and relates to a UV coating process for aluminum templates. Background Art
[0002] The full name of aluminum formwork is aluminum alloy formwork for concrete engineering. It is a new type of concrete engineering formwork. Compared with traditional wood formwork or steel formwork, aluminum formwork has the advantages of light weight, high strength, and easy assembly. It can effectively improve work efficiency and can be recycled many times. It conforms to the concept of green sustainable development and is widely used in the modern construction industry. However, in the actual engineering application process, the working environment of aluminum formwork is often relatively harsh. On the one hand, factors such as wind, rain, acid and alkaline atmosphere in the natural environment will cause etching to it. On the other hand, the strong alkaline concrete is also easy to corrode the aluminum formwork and react chemically, making the concrete and aluminum formwork bonded to each other and making it difficult to disassemble, thereby affecting the roughness of the concrete wall, reducing the quality of the project, and seriously affecting the repeated service life of the aluminum formwork and the recycling of the old formwork. Therefore, it is necessary to coat the surface of the aluminum formwork with an anti-corrosion coating to form a coating to protect the aluminum formwork, increase its corrosion resistance, improve the demoulding efficiency, and thus extend the service life of the aluminum formwork and improve the surface quality of the concrete wall. UV coating refers to a coating that is cured by UV radiation and is often used as a protective coating for aluminum formwork.
[0003] The bonding performance between the coating and the aluminum formwork and the performance of the coating itself directly affect the protective effect of the coating on the aluminum formwork. If the bonding performance between the coating and the aluminum formwork is poor and the coating has low adhesion, the coating will easily fall off or partially disappear, which will cause the aluminum formwork to lose protection. The better the performance of the coating itself, the more protective it can be against harsher environments.
[0004] Therefore, it is necessary to provide an aluminum template UV coating process to improve the adhesion of the coating to the aluminum template, while improving the strength of the coating itself, so that the coating can play a long-term protective effect and can cope with relatively harsh use environments. Summary of the invention
[0005] In order to overcome the problems in the background technology, the present invention polishes, corrodes, photocures, electronically cures, and other treatments on the surface of the aluminum template to effectively improve the adhesion between the coating and the aluminum template, while improving the coating's own strength and corrosion resistance, so that the coating can provide long-term protection for the aluminum template in a relatively harsh environment.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] The coating process comprises the following steps:
[0008] (1) Initial cleaning: Use an alkaline solution to clean and degrease the aluminum template, then rinse with clean water and dry to obtain a clean aluminum template.
[0009] (2) Electrochemical polishing: The clean aluminum template obtained in step (1) is immersed in a polishing liquid for electrochemical polishing, and then cleaned and dried to obtain a polished aluminum template.
[0010] (3) Surface microporous corrosion: an acidic corrosive liquid is applied to the working surface of the polished aluminum template obtained in step (2), and the polished aluminum template is corroded so that the working surface of the polished aluminum template obtains a microporous corrosion effect, and then the aluminum template is cleaned and dried to obtain a microporous aluminum template.
[0011] (4) Roll coating of a primer layer: Roll coating of a primer layer is performed on the microporous aluminum template obtained in step (3).
[0012] (5) Photocuring: Use a UVLED lamp to irradiate the aluminum template on which the primer layer is roller-coated in step (3) to cure the primer layer.
[0013] (6) Roll coating of thickening layer: Roll coating of thickening layer on the surface of the base material layer cured in step (5).
[0014] (7) Electron beam curing: After the thickening layer is roller-coated in step (6), the coating is deeply irradiated and cured by electron beam to complete the UV coating of the aluminum template.
[0015] Preferably, in step (1), the alkaline solution is a NaOH solution with a concentration of 30%, a solution temperature of 60±5° C., and an oil removal time of 90-120 s.
[0016] Preferably, in step (2), the polishing liquid is H 3 PO 4 , H 2 SO 4 , C 2 H 2 O 4 , H 2 O by volume H 3 PO 4 :H 2 SO 4 :C 2 H 2 O 4 :H 2 O=55:15:10:20 of mixed solution, polishing liquid temperature is 80~90℃, polishing time is 300-360s, H 3 PO 4 , H 2 SO 4 , C2 H 2 O 4 All were commercially available of analytical grade.
[0017] Preferably, in step (3), the acidic corrosive solution is an HF solution with a concentration of 40% to 50%.
[0018] Preferably, in step (3), the etching time of each surface of the aluminum template is 240-300s, and the etching liquid content on the surface of the aluminum template is 0.6±0.1mL / cm 2 The corrosion process is carried out in an environment with air humidity of 50-60%.
[0019] Preferably, in step (3), the depth of micropores on the surface of the aluminum template is 3 to 10 μm.
[0020] Preferably, in step (4), the thickness of the base material layer is 10 to 15 μm.
[0021] Preferably, in step (5), the power of the UVLED lamp is 100 W / cm 2 The distance between the UVLED lamp and the surface of the aluminum template is 10 to 15 cm, the curing time is 20 to 30 seconds, and the air humidity is maintained at 50% to 60% during the curing process.
[0022] Preferably, in step (6), the thickness of the thickened layer is 35 to 40 μm.
[0023] Preferably, in step (7), curing is carried out in a nitrogen atmosphere, the electron beam energy is 100 KeV, and the irradiation speed is 200 m / min.
[0024] In the above invention, if the aluminum template is just extruded, steps (1) and (2) can be omitted and the process can be directly started from step (3). In addition, the HF solution in the above invention can also be replaced by other solutions such as HCl solution, H 2 SO 4 Solution, H 2 C 2 O 4 Solution or mixed acid solution is used instead; to improve production efficiency, the aluminum template extrusion and the above-mentioned UV coating process can be connected in series to form an aluminum template extrusion-UV coating joint production line; therefore, the present invention includes but is not limited to the above content.
[0025] Beneficial effects of the present invention:
[0026] 1. The present invention removes impurities on the surface of the aluminum template by electrochemical polishing, which is conducive to the chemical reaction between the corrosive liquid and the aluminum template and promotes rapid corrosion; at the same time, after electrochemical polishing, the surface of the aluminum template has good macroscopic flatness, which can effectively reduce the unevenness of the coating thickness during roller coating.
[0027] 2. The present invention performs microporous corrosion on the working surface of the aluminum template to produce microscopic "pits" (i.e., micropores) on the surface of the aluminum template, thereby increasing the surface roughness of the aluminum template and the bonding area between the aluminum template and the UV coating, greatly enhancing the adhesion of the coating on the surface of the aluminum template and effectively reducing the probability of coating shedding.
[0028] 3. The present invention can ensure that the working surface of the aluminum template obtains microscopic "pits" that are evenly distributed and have a depth that reaches the target requirement by strictly controlling the corrosion time and the content of the corrosion liquid per unit area of the aluminum template, thereby avoiding the phenomenon of insufficient or excessive corrosion.
[0029] 4. Common aluminum alloy templates such as 6000 series and 7000 series usually contain magnesium. The present invention uses HF as the etching solution to allow the Mg element in the working surface area of the aluminum template to react with HF to generate MgF 2 , forming a corrosion cell, thereby shortening the corrosion time; at the same time, the aluminum template reacts with HF to generate It can inhibit the formation of an oxide film on the working surface of the aluminum template during the corrosion process, which helps to maintain the continuous progress of the corrosion reaction and achieve better corrosion effect.
[0030] 5. The present invention adopts a combination of light curing and electron beam curing, which can improve the strength of the coating on the one hand, and greatly enhance the adhesion between the coating and the aluminum template on the other hand, thereby preventing the coating from directly falling off during the operation of the aluminum template and causing the aluminum template to be exposed in the working environment. In this way, the coating can still provide long-term protection for the aluminum template in a relatively harsh environment, and is easy to demold and increase the service life of the template.
[0031] 6. The coating process of the present invention is simple and easy to implement, the coating cost is low, and it is easy to achieve mass production, which is suitable for industrial application and promotion. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the described contents.
[0033] Example 1
[0034] This embodiment uses the following process to complete the UV coating of the aluminum template:
[0035] (1) Initial cleaning: First, use a 30% by mass NaOH solution to remove oil. The solution temperature is controlled within the range of 60±5°C and the degreasing time is 90s. Then rinse with clean water and use a fan to dry to obtain a clean aluminum template.
[0036] (2) Electrochemical polishing: The clean aluminum template is placed in a volume ratio of H 3 PO4 :H 2 SO 4 :C 2 H 2 O 4 :H 2 Electrochemical polishing was carried out in a mixed solution of O=55:15:10:20, the polishing liquid temperature was controlled in the range of 80-90°C, the polishing time was 300s, and then rinsed with clean water and dried with a blower to obtain a polished aluminum template.
[0037] (3) Surface microporous corrosion: The polished aluminum template was placed on a working platform with a horizontality of 0.04 mm / m, and then a 40% HF solution was applied to its working surface for surface microporous corrosion. The coating time of the corrosion solution did not exceed 3 s, the adhesion time of the corrosion solution was 240 s, and the corrosion solution content on the aluminum template surface was 0.6 ± 0.1 mL / cm 2 During the reaction process, the air humidity was maintained at 55%. After the corrosion was completed, the aluminum template was immediately rinsed with clean water and dried with a blower, and then sent to a drying oven for drying. The final microscopic "pits" (micropores) had a depth in the range of 3-10μm, and a microporous aluminum template was obtained.
[0038] (4) Primer layer roller coating: Place the microporous aluminum template on the working platform of the roller coating equipment for primer layer roller coating, the primer layer thickness is 10 μm. The primer layer thickness can be directly set by the roller coating machine.
[0039] (5) Light curing: After the base material layer is roller coated, a UVLED lamp is used to cure the base material layer. The light power of the lamp is 100W / cm 2 , the distance between the lamp tube and the surface of the aluminum template is 10 cm, the curing time is 20 seconds, the curing temperature is 40°C, and the air humidity is 55%.
[0040] (6) Thickening layer roller coating: A thickening layer roller coating is performed on the surface of the cured base material layer, and the thickness of the thickening layer is 35 μm.
[0041] (7) Electron beam curing: After the thickened layer is rolled to meet the coating thickness requirement, electron beam is used for deep curing to improve the hardness and adhesion of the coating. The curing process is carried out in a nitrogen atmosphere with an electron beam energy of 100 KeV and an irradiation speed of 200 m / min. The coating is completed.
[0042] Example 2
[0043] This embodiment uses the following process to complete the UV coating of the aluminum template:
[0044] (1) Initial cleaning: First, use a 30% by mass NaOH solution to remove oil. The solution temperature is controlled within the range of 60±5°C and the degreasing time is 120s. Then rinse with clean water and use a fan to dry to obtain a clean aluminum template.
[0045] (2) Electrochemical polishing: The clean aluminum template is placed in a volume ratio of H 3 PO 4 :H 2 SO 4 :C 2 H 2 O 4 :H 2 Electrochemical polishing was carried out in a mixed solution of O=55:15:10:20, the polishing liquid temperature was controlled in the range of 80-90°C, the polishing time was 360s, and then rinsed with clean water and dried with a blower to obtain a polished aluminum template.
[0046] (3) Surface microporous corrosion: The polished aluminum template was placed on a working platform with a horizontality of 0.04 mm / m, and then a 45% HF solution was applied to its working surface for surface microporous corrosion. The coating time of the corrosion solution did not exceed 3 s, the adhesion time of the corrosion solution was 300 s, and the corrosion solution content on the aluminum template surface was 0.6 ± 0.1 mL / cm 2 During the reaction process, the air humidity is maintained at 50%. After the corrosion is completed, the aluminum template is immediately rinsed with clean water and blown dry with a fan, and then sent to a drying oven for drying. The final microscopic "pits" (micropores) have a depth in the range of 3-10μm, and a microporous aluminum template is obtained.
[0047] (4) Primer layer roller coating: Place the microporous aluminum template on the working platform of the roller coating equipment for primer layer roller coating, with a primer layer thickness of 15 μm. The primer layer thickness can be directly set by the roller coating machine.
[0048] (5) Light curing: After the base material layer is roller coated, a UVLED lamp is used to cure the base material layer. The light power of the lamp is 100W / cm 2 , the distance between the lamp tube and the surface of the aluminum template is 15 cm, the curing time is 30 seconds, the curing temperature is 40°C, and the air humidity is 50%.
[0049] (6) Thickening layer roller coating: A thickening layer roller coating is performed on the surface of the cured base material layer, and the thickness of the thickening layer is 40 μm.
[0050] (7) Electron beam curing: After the thickened layer is rolled to meet the coating thickness requirement, electron beam is used for deep curing to improve the hardness and adhesion of the coating. The curing process is carried out in a nitrogen atmosphere with an electron beam energy of 100 KeV and an irradiation speed of 200 m / min. The coating is completed.
[0051] Example 3
[0052] This embodiment uses the following process to complete the UV coating of the aluminum template:
[0053] (1) Initial cleaning: First, use a 30% by mass NaOH solution to remove oil. The solution temperature is controlled within the range of 60±5°C and the degreasing time is 100s. Then rinse with clean water and use a fan to dry to obtain a clean aluminum template.
[0054] (2) Electrochemical polishing: The clean aluminum template is placed in a volume ratio of H 3 PO 4 :H 2 SO 4 :C 2 H 2 O 4 :H 2 Electrochemical polishing was carried out in a mixed solution of O=55:15:10:20, the polishing liquid temperature was controlled in the range of 80-90°C, the polishing time was 330s, and then rinsed with clean water and dried with a blower to obtain a polished aluminum template.
[0055] (3) Surface microporous corrosion: The polished aluminum template was placed on a working platform with a horizontality of 0.04 mm / m, and then a 50% HF solution was applied to its working surface for surface microporous corrosion. The coating time of the corrosion solution did not exceed 3 s, the adhesion time of the corrosion solution was 280 s, and the corrosion solution content on the aluminum template surface was 0.6 ± 0.1 mL / cm 2 During the reaction process, the air humidity is maintained at 60%. After the corrosion is completed, the aluminum template is immediately rinsed with clean water and blown dry with a fan, and then sent to a drying oven for drying. The final microscopic "pits" (micropores) have a depth in the range of 3-10μm, and a microporous aluminum template is obtained.
[0056] (4) Primer layer roller coating: Place the microporous aluminum template on the working platform of the roller coating equipment for primer layer roller coating, the primer layer thickness is 12 μm. The primer layer thickness can be directly set by the roller coating machine.
[0057] (5) Light curing: After the base material layer is roller coated, a UVLED lamp is used to cure the base material layer. The light power of the lamp is 100W / cm 2 , the distance between the lamp tube and the surface of the aluminum template is 12 cm, the curing time is 25 s, the curing temperature is 40°C, and the air humidity is 60%.
[0058] (6) Thickening layer roller coating: A thickening layer roller coating is performed on the surface of the cured base material layer, and the thickness of the thickening layer is 38 μm.
[0059] (7) Electron beam curing: After the thickened layer is rolled to meet the coating thickness requirement, electron beam is used for deep curing to improve the hardness and adhesion of the coating. The curing process is carried out in a nitrogen atmosphere with an electron beam energy of 100 KeV and an irradiation speed of 200 m / min. The coating is completed.
[0060] Comparative Example 1
[0061] This comparative example adopts the same process as Example 1 for UV coating, except that: in this comparative example, manual polishing is used instead of electrochemical polishing.
[0062] Comparative Example 2
[0063] This comparative example adopts the same process as Example 1 for UV coating, except that: in this comparative example, surface microporous corrosion is not performed, and the base material layer is directly roller-coated after electrochemical polishing.
[0064] Comparative Example 3
[0065] This comparative example adopts the same process as Example 1 for UV coating, except that: in this comparative example, the content of the corrosive liquid on the surface of the aluminum template is 0.2 mL / cm 2 ,After corrosion, the depth of the microscopic "pits" is in the range of 2-3μm.
[0066] Comparative Example 4
[0067] This comparative example adopts the same process as Example 1 for UV coating, except that: in this comparative example, the content of the corrosive liquid on the surface of the aluminum template is 1.0 mL / cm 2 , after corrosion, the microscopic "pits" are connected into sheets.
[0068] Comparative Example 5
[0069] The surface of the aluminum template in this comparative example was not roller-coated.
[0070] The following tests were performed on the aluminum templates of Examples 1-3 and Comparative Examples 1-5, and the results were shown in Table 1.
[0071] 1. Simulated rainwater erosion test: Use dilute H with a pH value of 6 2 SO 4 The aluminum formwork was rinsed with the solution for 48 hours to simulate the process of rainwater scouring the aluminum formwork in the natural environment, and the surface quality of the aluminum formwork was observed.
[0072] 2. Coating corrosion resistance test: Test according to standard GB / T4893.1-1985 furniture surface paint film liquid resistance determination method.
[0073] 3. Paint adhesion test: Test according to the standard GB / T4893.4-2013 adhesion cross-cutting test method.
[0074] 4. Paint knocking test: Use an automatic knocking device to continuously knock on the surface of the aluminum template, set the knocking force to 1kg, and record the number of knocks when the coating falls off.
[0075] 5. Concrete demoulding test: Apply wet concrete to the surface of the aluminum formwork, remove it after the concrete dries and place new concrete. Repeat this experiment and record the number of experiments when coating damage occurs.
[0076] Table 1
[0077]
[0078]
[0079] It can be seen from Table 1 that the anti-corrosion coating on the surface of the aluminum formwork in the embodiments of the present invention has excellent comprehensive properties, including resistance to rain erosion, corrosion resistance, adhesion, resistance to knocking, and resistance to concrete corrosion.
[0080] The surface coating of the aluminum formwork of Comparative Example 1 has poor resistance to rain erosion, corrosion resistance, adhesion, knock resistance, and concrete corrosion resistance. The reason is that the macro-flatness of the aluminum formwork after manual polishing is relatively poor, and the impurity layer at the corners is not completely polished, resulting in uneven thickness and distribution of the coating at different positions. The adhesion between the coating and the aluminum formwork is poor in the area where impurities remain, which can easily lead to local detachment and subsequent expansion.
[0081] The adhesion, knock resistance and concrete corrosion resistance of the aluminum formwork surface coating of Comparative Example 2 are lower than those of Example 1. The reason is that the surface roughness of the polished aluminum formwork is low, the adhesion of the coating on the smooth surface is poor, and the anti-corrosion coating is very easy to fall off during the process of being knocked and separating the concrete.
[0082] The adhesion, knock resistance, and concrete corrosion resistance of the aluminum formwork surface coating of Comparative Examples 3 and 4 are lower than those of Example 1. The reason is that a lower content of corrosive liquid will result in shallower corrosion "pits", while a higher content of corrosive liquid will cause the corrosion "pits" to be connected into sheets, both of which will weaken the adhesion effect of the coating.
[0083] In summary, the coating process of the present invention adopts a reasonable coating process and optimized process parameters, so that after coating is completed, the coating itself has excellent performance, and at the same time significantly improves the adhesion between the coating and the aluminum template, so that the coating can play a long-term protective role on the aluminum template in a harsh environment, thereby improving the demoulding efficiency and the service life of the aluminum template.
[0084] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A UV coating process for aluminum templates, characterized by: The coating process comprises the following steps: (1) Initial cleaning: Use an alkaline solution to clean and degrease the aluminum template, then rinse with clean water and dry to obtain a clean aluminum template; (2) electrochemical polishing: immersing the clean aluminum template obtained in step (1) in a polishing solution for electrochemical polishing, and then washing and drying to obtain a polished aluminum template; (3) Surface microporous corrosion: applying an acidic corrosive liquid to the working surface of the polished aluminum template obtained in step (2), corroding the polished aluminum template so that the working surface of the polished aluminum template obtains a microporous corrosion effect, and then cleaning and drying the aluminum template to obtain a microporous aluminum template; (4) Roll coating of a primer layer: Roll coating of a primer layer on the working surface of the microporous aluminum template obtained in step (3); (5) Photocuring: using a UVLED lamp to irradiate the aluminum template on which the primer layer is roller-coated in step (3) to cure the primer layer; (6) thickening layer roller coating: roller coating the thickening layer on the surface of the base material layer cured in step (5); (7) Electron beam curing: After the thickening layer is roller-coated in step (6), the coating is deeply irradiated and cured by electron beam to complete the UV coating of the aluminum template.
2. The coating process according to claim 1, characterized in that: In the step (1), the alkaline solution is a NaOH solution with a concentration of 30%, a solution temperature of 60±5° C., and an oil removal time of 90-120 seconds.
3. The coating process according to claim 1, characterized in that: In the step (2), the polishing liquid is a mixed solution of H3PO4, H2SO4, C2H2O4, and H2O in a volume ratio of H3PO4:H2SO4:C2H2O4:H2O=55:15:10:20, the polishing liquid temperature is 80-90°C, and the polishing time is 300-360s.
4. The coating process according to claim 1, characterized in that: In the step (3), the acidic corrosive solution is an HF solution with a concentration of 40% to 50%.
5. The coating process according to claim 1, characterized in that: In step (3), the etching time of each surface of the aluminum template is 240-300s, and the etching liquid content on the surface of the aluminum template is 0.6±0.1mL / cm 2 The corrosion process is carried out in an environment with air humidity of 50-60%.
6. The coating process according to any one of claims 1, 4 and 5, characterized in that: In the step (3), the depth of the micropores on the surface of the aluminum template is 3 to 10 μm.
7. The coating process according to claim 1, characterized in that: In the step (4), the thickness of the base material layer is 10 to 15 μm.
8. The coating process according to claim 1, characterized in that: In step (5), the power of the UVLED lamp is 100 W / cm 2 The distance between the UVLED lamp and the surface of the aluminum template is 10 to 15 cm, the curing time is 20 to 30 seconds, and the air humidity is maintained at 50% to 60% during the curing process.
9. The coating process according to claim 1, characterized in that: In the step (6), the thickness of the thickened layer is 35 to 40 μm.
10. The coating process according to claim 1, characterized in that: In the step (7), curing is performed in a nitrogen atmosphere, the electron beam energy is 100 KeV, and the irradiation speed is 200 m / min.
Citation Information
Patent Citations
Aluminum alloy valve with composite coating and its surface treating method
CN101086063A
Method for preparing ordered micropore structure on stainless steel surface
CN104562052A
Aluminum template with coating and preparation method thereof
CN117282632A
Aluminium alloy, a support of lithographic printing plate and a lithographic printing plate using the same
EP0096347A2
Printing plate and plate making method
US20040118308A1